Effects of acute kidney injury after liver resection on long-term outcomes - Seiji Ishikawa; Manami Tanaka; Fumi Maruyama; Arisa Fukagawa; Nobuhiro Shiota; Satoshi Matsumura; Koshi Makita (Korean Journal of Anesthesiology, 2017)
BackgroundTo investigate the effects of acute kidney injury (AKI) after liver resection on the long-term outcome, including mortality and renal dysfunction after hospital discharge.MethodsWe conducted a historical cohort study of patients who underwent liver resection for hepatocellular carcinoma with sevoflurane anesthesia between January 2004 and October 2011, survived the hospital stay, and were followed for at least 3 years or died within 3 years after hospital discharge. AKI was diagnosed based on the Acute Kidney Injury Network classification within 72 hours postoperatively. In addition to the data obtained during hospitalization, serum creatinine concentration data were collected and the glomerular filtration rate (GFR) was estimated after hospital discharge.ResultsAKI patients (63%, P = 0.002) were more likely to reach the threshold of an estimated GFR (eGFR) of 45 ml/min/1.73 m2 within 3 years than non-AKI patients (31%) although there was no significant difference in mortality (33% vs. 29%). Cox proportional hazard regression analysis showed that postoperative AKI was significantly associated with the composite outcome of mortality or an eGFR of 45 ml/min/1.73 m2 (95% CI of hazard ratio, 1.05–2.96, P = 0.033), but not with mortality (P = 0.699), the composite outcome of mortality or an eGFR of 60 ml/min/1.73 m2 (P =0.347).ConclusionsAfter liver resection, AKI patients may be at higher risk of mortality or moderate renal dysfunction within 3 years. These findings suggest that even after discharge from the hospital, patients who suffered AKI after liver resection may need to be followed-up regarding renal function in the long term.